Adaptive transformations in subtitle translation: an eco-translatology analysis of Hi, Mom - Yanan, Yang; Abdullah, Muhammad Alif Redzuan; Syed Abdullah, Syed Nurulakla (Human Resources Management Academic Research Society (HRMARS), 2024)
Eco-translatology is a translation theory that was proposed by Chinese scholar Professor Hu Gengshen, which views translation as a process of adaptation and selection within a complex ecological environment comprising linguistic, cultural, and communicative dimensions. In recent years, with the growing global reach of the film industry, subtitle translation has become more important for the development of Chinese films on the international stage. As one of the key links in cross-cultural communication, the quality of film subtitle translation affects the box office and viewing experience. Hi, Mom, a widely acclaimed Chinese family comedy, topped China’s box office during the Chinese New Year in 2021 and ascended to the third place in the global box office, and high-quality subtitle translation is indispensable to its success. Based on the theoretical framework of Eco-translatology theory, this study discusses the subtitle translation of Hi, Mom to analyze translators’ adaptive transformation in linguistic, cultural, and communicative dimensions. By selecting and analyzing ten representative examples from key scenes and dialogues, the findings show that in the translation process of Hi, Mom’s subtitles, different translation techniques were adopted that include the applications of amplification, omission, free translation, cultural substitution and explicitation to achieve adaptive transformations in the linguistic, cultural, and communicative dimensions. These insights contribute to the growing body of research on Eco-translatology and offer practical guidelines for improving subtitle translation practices to better engage international audiences.